The Monotheist Laozi - Hashmi, Arshad Masood (Journal of Maobi, 2025)
The enclosed article, “The Monotheist Laozi” seeks to explore Laozi’s Dao De Jing through a comparative theological framework, with particular emphasis on its affinities with Islamic spirituality and Sufi metaphysics. The paper argues that Laozi’s vision was essentially monotheistic, and that later ritualistic and polytheistic interpretations were historical accretions rather than original doctrine. The study employs a comparative exegetical method, drawing on both primary Daoist sources and Qur’ānic concepts such as istighnā, taqwa, sulook, ḥaqīqah, maʿrifah, and faḍl. It also considers Indo-Islamic perspectives, particularly Maulana Abul Kalam Azad’s recognition of Laozi as a prophet-like figure. The Dao De Jing presents the Dao as an absolute, ineffable source of all existence, with spiritual practice emphasizing humility, self-effacement, and alignment with its natural order—paralleling the Qur’anic notions of tawḥīd and taslīm. In governance and ethics, the Daoist sage embodies restraint, moral integrity, and intuitive action, showing that true authority and freedom arise from ego-effacement and surrender to a transcendent principle.